PENGOLAHAN AIR BERSIH GUNA MENURUNKAN KADAR KAPUR (KESADAHAN) MENGGUNAKAN TENAGA SURYA (SOLAR CELL) UNTUK MENGURANGI RESIKO TERKENA BATU GINJAL PADA MASYARAKAT DESA SUMBERWUNGU - Gatot Santoso; P. Wisnubroto; Slamet Hani (Universitas Sahid Surakarta, 2020)
The quality of PDAM water used by the community of Sumberungu Village, Tepus Subdistrict, Gunung Kidul Regency has a hardness content (lime) of 222.3 mg / L (from laboratory tests) in a high classification (hard). If the user is old enough to cause kidney disorders (kidney stones). Based on the above, to reduce the level of lime (hardness) and save on the cost of clean water treatment, it is necessary to make clean water treatment equipment using solar cells that are environmentally friendly for the partner community groups. The construction of clean water treatment equipment that was designed by the Community Partnership Program Team (PKM) is expected to reduce the level of lime and save costs, then the hardness in water in the partner community groups can decrease. In the end it can improve the health and well-being of partner community groups and the community in general. The results of observations in the field of clean water pengolan tool in order to reduce levels of lime that is designed is able to process raw water from Sumberwungu Village which has a hardness content of 222.3 mg / L. After entering into the treatment of clean water, the hardness content becomes 76 mg / L. 429/120. So from these results there was a decrease in hardness rate of 146.2 mg / L.